Efficacy of cabazitaxel rechallenge in heavily treated patients with metastatic castration-resistant prostate cancer. (July 2018) - Thibault, Constance; Eymard, Jean-Christophe; Birtle, Alison; Krainer, Michael; Baciarello, Giulia; Fléchon, Aude; Le Moulec, Sylvestre; Spaeth, Dominique; Laguerre, Brigitte; Caffo, Orazio; Deville, Jean-Laurent; Beuzeboc, Phillipe; et al.
Abstract: Background: Treatment option in patients with metastatic castration-resistant prostate cancer (mCRPC) previously treated with docetaxel (DOC), cabazitaxel (CABA) and new hormone therapy (NHT) is limited. Rechallenge with DOC is limited because of cumulative toxicities. This study investigated the activity and safety of CABA rechallenge in mCRPC. Patients and methods: Clinical data were collected retrospectively in 17 centres in Europe. Eligible patients had undergone rechallenge with cabazitaxel after three previous lines of treatment (DOC, NHT and CABA, in any order). Overall survival (OS) and progression-free survival (PFS) were estimated by the Kaplan–Meier method. Data on toxicities were collected. Results: A total of 69 of 562 patients (Eastern Cooperative Oncology Group performance status 0–1 69%) were rechallenged with CABA (25 mg/m 2 q3w, 58%; 20 mg/m 2 q3w, 27.5%; other, 14.5%) for 1–10 (median 6) cycles; 76.8% received prophylactic granulocyte colony-stimulating factor. Median radiological or clinical PFS with CABA rechallenge was 7.8 months and 11.9 months with initial CABA therapy. OS was 13.7 months (95% confidence interval [CI]: 9.3–15.7) from the first CABA rechallenge cycle, 59.9 months (47.8–67.1) from the first life-extending therapy in mCRPC and 78.3 months (66.4–90.7) from mCRPC diagnosis. Best clinical benefit was improved (34.3%) or stable (47.8%). Lack of response to rechallenge occurred in 17.9% of patients (3.1% with initial CABA). The level of prostate-specific antigen decreased by ≥ 50% in 24% of patients at rechallenge (71% with initial CABA). There was no grade ≥III peripheral neuropathy or nail disorders. Conclusions: CABA rechallenge may be a treatment option without cumulative toxicity in heavily pretreated patients with mCRPC who are still fit and had a progression >3 months after the last CABA injections. Highlights: Cabazitaxel rechallenge is a feasible treatment option in heavily pretreated patients with metastatic castration-resistant prostate cancer. The initial response rate to cabazitaxel rechallenge is good. Rechallenge with cabazitaxel has a manageable tolerability profile.